Genome-Wide Analysis of NF-Y Genes in Potato and Functional Identification of StNF-YC9 in Drought Tolerance - Li, Shigui; Zhang, Ning; Zhu, Xi; Ma, Rui; Liu, Shengyan; Wang, Xiao; Yang, Jiangwei; Si, Huaijun (Frontiers in Plant Science, 2021)
The nuclear factor Y (NF-Y) family is comprised of transcription factors that have been implicated in multiple plant biological processes. However, little is known about this family in potato. In the present study, a total of 41 StNF-Y genes were identified in the potato genome. In addition, the phylogenetic, gene struture, motif and chromosomal location of this family were analyzed. The tissue expression profiles based on RNA-seq data showed that 27 StNF-Y genes had tissue-specific expression, while the remaining 14 had low expression in all tissues. Publicly available transcriptomics data from various abiotic stresses revealed several stress-responsive StNF-Y genes, which were further verified via quantitative real-time polymerase chain reaction experiments. Furthermore, the StNF-YC9 gene was highly induced by dehydration and drought treatments. StNF-YC9 protein was mainly localized in the nucleus and cytoplasmic membrane. Overexpressing StNF-YC9 potato lines (OxStNF-YC9) had significantly increased in root length and exhibited stronger stomatal closure in potato treated by polyethylene-glycol and abscisic acid. In addition, OxStNF-YC9 lines had higher photosynthetic rates and decreased water loss under short-term drought stress compared to wild-type plants. During long-term drought stress, OxStNF-YC9 lines had higher proline levels, lower malondialdehyde content and increased activity of several antioxidant enzymes, including superoxide dismutase, catalase and peroxidase. This study increased our understanding of the StNF-Y gene, and suggested that StNF-YC9 played an important role in drought tolerance by increased the photosynthesis rate, antioxidant enzyme activity and proline accumulation coupled to lowered malondialdehyde accumulation in potato.